Long –term monitoring of the glaciers in Wordie Bay, Antarctic Peninsula, using multi-mission SAR time series - Friedl, Peter; Seehaus, Thorsten; Wendt, Anja; Braun, Matthias (2016)
The Antarctic Peninsula is one of the world`s most affected regions by Climate Change. Dense and long time series of multi-mission SAR data enable detailed studies of the rapid glaciological changes in this area. We present first results of a case study at the former Wordie Ice Shelf, located at the south-western side of the Antarctic Peninsula. Since the ice shelf disintegrated in a series of events during the 1980s, only disconnected and retreating tidewater glaciers have remained. Due to the loss of the buttressing force of the ice shelf, the former tributary glaciers reacted with an acceleration of their flow speeds in order to adapt to the new boundary conditions. While the loss of the ice shelf itself does not affect sea level, the increased outflow of the glaciers and the associated mass loss contribute to global sea level rise. Most of the studies conducted at Wordie Bay so far covered only relatively short investigation periods and compared their results on a bi-temporal basis. Hence it is yet neither well known how long this process of adaption to the new boundary conditions exactly lasts nor how much ice mass loss and sea level rise is caused by this process in total. We provide completest possible time series of glaciological parameters (e.g. glacier extends, grounding line positions, flow speeds, glacier mass flow, glacier elevation/volume changes and contributions to global sea level rise) for the glaciers in Wordie Bay, ranging from the mid-1990s to today. The glaciological parameters are determined by applying intensity tracking as well as differential interferometric synthetic radar (DInSAR) methods and differential range offset tracking. For this purpose large datasets of previously active (e.g. ERS, Envisat-ASAR, RADARSAT-1, ALOS PALSAR) as well as currently recording SAR sensors (e.g. Sentinel-1, TerraSAR-X, TanDEM-X) are processed together with data from laser/radar altimetry and ground penetrating radar. The usage of long-term series of SAR data allows us to obtain more precise series of ...